AN ANALYSIS ON DEIXIS IN THE SONG LYRICS OF JUSTIN BIEBER’S “MY WORLD” ALBUM - Ratri Yuliningrum; Zulfa Afis Sunani; Anginna Birochmatika (Faculty of Education and Teachers Training, 2020)
This study aimed to analyze the type of deixis in the song lyrics of Justin Bieber's